Comparison of ultrasound vector flow imaging and CFD simulations with PIV measurements of flow in a left ventricular outflow trackt phantom - Implications for clinical use and in silico studies - Leinan, Paul Roger; Grønli, Thomas; Skjetne, Paal; Wigen, Morten Smedsrud; Urheim, Stig; Lovstakken, Lasse; Dahl, Sigrid K. (Computers in biology and medicine, 2022)
In this study we have compared two modalities for flow quantification from measurement data; ultrasound (US) and shadow particle image velocimetry (PIV), and a flow simulation model using computational fluid dynamics (CFD). For the comparison we have used an idealized Quasi-2D phantom of the human left ventricular outflow tract (LVOT). The PIV data will serve as a reference for the true flow field in our setup. Furthermore, the US vector flow imaging (VFI) data has been post processed with model-based regularization developed to both smooth noise and sharpen physical flow features. The US VFI flow reconstruction results in an underestimation of the flow velocity magnitude compared to PIV and CFD. The CFD results coincide very well with the PIV flow field maximum velocities and curl intensity, as well as with the detailed vortex structure, however, this correspondence is subject to exact boundary conditions. •Novel ultrasound vector flow imaging technique compared to flow phantom and CFD.•Simultaneous ultrasound vector flow imaging and flow phantom velocity data.•Combined flow phantom and CFD provide added benefit in ultrasound imaging development.